ANALYSIS OF TRANSIENT AND FREQUENCY RESPONSES OF MODIFIED RLC ELECTRICAL CIRCUIT WITH DAMPING AND FILTERING CHARACTERISTICS - Okafor, Linus U.; Oyetoro, Julius Akintayo (FUDMA JOURNAL OF SCIENCES, 2025)
In this paper we address the problem occurring in electrical circuit with discontinuity in power source, using the Heaviside function to represent the switches (on/off) existing in the electrical circuit component. Thus, this paper presents an analytical and simulation-based study of modified RLC circuits, focusing on their transient and frequency responses, using Laplace transform techniques and Heaviside step input modeling, the research evaluates underdamped, undamped, overdamped, and critically damped behaviors and the frequency domain analysis using the Bode plots  to reveals the filtering characteristics of RC and RLC configurations. The paper highlights how component values influence energy dissipation, signal attenuation, and resonance. The findings provide useful guidelines for circuit design in signal processing and communications.
Keywords: RLC circuit; Transient response; Frequency response; Damping; Filtering; Laplace transform; Heaviside function; MATLAB simulation